ART special issue: Social rebirth and social transformation? Rebuilding social lives after ART in rural Uganda - Janet, Seeley; S. Russell (Aids Care, 2010)
This paper examines how HIV diagnosis, illness and anti-retroviral therapy (ART) have an impact on the social dimensions of people's lives in rural Uganda, focusing on identity, relationships and membership of groups. Using concepts drawn from sociological research on experiences of illness and recovery, “getting back to normal”, “rebirth” and “turning point”, we present findings from qualitative research that explored the social changes brought about by HIV and ART among 70 men and women taking ART since 2003. With a second chance at life, some people's narratives revealed a pursuit of getting “back to normal”, restoring and resuming their place in their families and communities. Others sought to change or transform their new lives, what we term a “social rebirth”, moving away from old social networks and lifestyles. Regaining health was associated with a desire to make the most of life by joining social groups and civil society organisations, establishing new relationships and advising and supporting others. However, earlier losses of family and friends due to AIDS-related deaths made “social rebirth” hard for many people. Our findings also show that the process of responding to ART is not linear and the pursuit of change following diagnosis and treatment may be difficult to sustain, as the months and years on ART progress and the struggles of getting on with life take their toll. Sustaining social rebirth was challenging and complex due to the nature of HIV infection itself (for example, new intimate relationships pose challenges) and the harsh economic environment. Maintaining changed lives for those living with HIV and ART is important because this will contribute to better disease self-management and so demands an understanding by support organisations of the nature of these changes and challenges.